KAMPUNG HARMONISASI ANTAR PEMELUK AGAMA BERBASIS DALIHAN NA TOLU - Indra, Indra Muda; Marlina Deliana, Armansyah Matondang, (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
Harmonious village is a village inhabited by people from different ethnicities, tribes, clans, and religions who can coexist peacefully. The research problem is why the people of Sibadoar village are committed to preserving the harmonious village, and whether there are threats to preserving Sibadoar village as a harmonious village. To obtain data, a qualitative descriptive research method was used with data collection techniques such as in-depth interviews, direct observations, Focus Group Discussion (FGD), and literature review. The research informants included the Subdistrict Head of Sipirok, the Head of Sibadoar Village, the chairman of the Interfaith Communication Forum of Sipirok, village officials, non-official village groups, including community leaders, religious leaders, traditional leaders, and youth leaders who are knowledgeable about the subject under investigation. Based on the research, the commitment of the community to preserve the status of the Harmonious Village is primarily due to the sense of kinship within the Dalihan Na Tolu bond. With this concept, they feel like a unified entity, so any shortcomings of their fellow villagers must be forgiven because it would bring shame to the village residents. The Dalihan Na Tolu tradition has a strong influence on the daily activities of the community, including customary rituals, whether they involve celebrations (siriaon) or mourning (siluluton). In conclusion, the community has a strong desire to maintain the status of a harmonious village. However, slowly, the development of technology, transportation, and information has affected the determination of the community to maintain the status of a harmonious village, especially among the younger generation.